THE OVER-EXPOSURE OF GEOGRAPHIC INFORMATION ABOUT INSTALLATIONS OF INTEREST FOR DEFENCE IN THE NETWORK - Rubio, Yaiza; Brezo, Félix (Journal of the Spanish Institute for Strategic Studies, 2013)
Geographic information could be a problem when it displays infrastructuresof interest to defence and governments do not have tools to control theirdiffusion. In order to face this difficulty, we have collected informationabout more than forty military bases in different countries and we havedeveloped a methodology for the evaluation of such information. In addition,the authors propose the creation of an indicator measuring the exposurelevel of the observed infrastructures to determine the extent to whichthis compromises their safety. Therefore, we find appropriate to include themonitoring of images provided by mapping services in counterintelligenceplans and the establishment of an international framework that could manageneutrally the geographic information available on the Internet.nd theability of actors who use it.